Bibliometric Analysis of the Effectiveness of Accountability in Public Policy - Judijanto, Loso; Qosim, Nanang; Saparman, Saparman; Suhariyanto, Didik (West Science Interdisciplinary Studies, 2025)
This study conducts a bibliometric analysis to explore the scholarly landscape on the effectiveness of accountability in public policy, focusing on literature indexed in Scopus. Using VOSviewer, the study visualizes thematic clusters, co-authorship networks, and country collaborations, offering insights into key trends, influential authors, and global research dynamics. Accountability emerges as a central concept, closely linked to transparency, governance, and public trust, with significant applications in sectors such as healthcare, education, and sustainable development. The analysis reveals the interdisciplinary nature of accountability research while highlighting gaps in addressing digital governance and underrepresented regional perspectives. The findings emphasize the importance of robust accountability frameworks in enhancing public policy effectiveness and the need for integrative and inclusive research to address contemporary governance challenges. This study provides valuable insights for academics and policymakers, offering a foundation for advancing accountability frameworks in diverse governance contexts.